Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.18267/j.pep.443
|View full text |Cite
|
Sign up to set email alerts
|

Do E-Auctions Realy Improve the Efficiency of Public Procurement? The Case of the Slovak Municipalities

Abstract: Abstract:The article deals with the factors which infl uence effi ciency of public procurement in the competitive contracting conducted through e-auctions in 15 Slovak cities. Data cover building and IT contracts awarded in the years [2007][2008][2009]. Together 186 observations were used for the analysis. The article starts with a theoretical discussion on the factors infl uencing effi ciency of the procurement including potential impacts of the e-procurement and the e-auction. Than fi ve hypotheses are formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Reference [16] found that the level of participation of the auction participants in the procurement of goods and services for Turkish government is relatively higher than the procurement of construction projects. On the other hand, [24] found that there is no significant difference in the number of auction participants for the procurement of building works, the procurement of transportation infrastructures and the procurement of information and technology. Based on the preceding explanation, we subsequently propose the following hypothesis (H 2 ): H 2 : Type of procurement has an effect on the number of auction participants…”
Section: Procurement Type and The Number Of Auctionmentioning
confidence: 93%
“…Reference [16] found that the level of participation of the auction participants in the procurement of goods and services for Turkish government is relatively higher than the procurement of construction projects. On the other hand, [24] found that there is no significant difference in the number of auction participants for the procurement of building works, the procurement of transportation infrastructures and the procurement of information and technology. Based on the preceding explanation, we subsequently propose the following hypothesis (H 2 ): H 2 : Type of procurement has an effect on the number of auction participants…”
Section: Procurement Type and The Number Of Auctionmentioning
confidence: 93%
“…They conclude that allowing foreign participants to participate in the auction and the threshold value for conducting an auction have notable effects on the number of bidders and the auction price. Based on the auction data from Slovak municipalities, Pavel et al (2013) investigate the factors that may affect the auction prices and the efficiency of e-auctions. Their work shows that each additional bid submitted in the auction leads to a decrease in the auction price.…”
Section: E-auction Studies With the Public Sector Datasetsmentioning
confidence: 99%
“…As a result, in the literature, the number of studies focused on the factors that have notable effects on the buyer surplus has increased significantly. In this research stream, typically, the impacts of the number of bidders (Millet et al 2004, Mithas and Jones 2007, Park et al 2012, Onur et al 2012, Gurakar and Taş 2015, Raventós and Zolezzi 2015, the number of submitted bids (Millet et al 2004, Mithas and Jones 2007, Pavel et al 2013, Raventós and Zolezzi 2015, the amount of auctioning item (Bapna et al 2003, Koppius et al 2004, Pearcy and Giunipero 2006, Park et al 2012, the auction duration (Mithas andJones 2007, Raventós andZolezzi 2015), the reservation price (Bapna et al 2003, Kauffman and Wood 2006, Mithas and Jones 2007, Onur et al 2012, Pavel et al 2013, the ranking information during the auction (Millet et al 2004, Mithas and Jones 2007, Elmaghraby et al 2012, Tunca et al 2014, Setia and Speier-Pero 2015, the information about the auctioning item -description, photo, etc.- (Koppius et al 2004, Kauffman and Wood 2006, Stoll and Zöttl 2014, the non-price attributes of the auctioning item (Koppius et al 2004, Engelbrecht et al 2007, Haruvy and Katok 2013, Tunca et al 2014, Stoll and Zöttl 2014, Moretti and Valbonesi 2015, and the supplier incumbe...…”
Section: Research Framework and Questionsmentioning
confidence: 99%
“…Vlivem počtu uchazečů na vysoutěženou cenu se zabývají rovněž Nemec a Grega (2015) či v případě zakázek na elektřinu a zemní plyn Soudek a Skuhrovec (2013). Vliv elektronických aukcí na efektivnost zadávání veřejných zakázek zkoumají Pavel, Sičáková-Beblavá (2013). Ochrana a Pavel (2013) potom analyzují problematiku transparentnosti a korupce ve veřejných zakázkách.…”
Section: Teoretická Východiskaunclassified